Virtual sensor system for monitoring and detection of critical modes for the prevention of accidents in production - Milanoski, Nikola; Vasilev, Velimir; Petrov, Georgi (Yearbook Telecommunications, 2022)
Many enterprises with new and experimental processing plants use SCADA systems to control machinary, but these systems are not always complete, this is often due to financial or purely technological constraints or ignorance of the overall process at the time of its introduction. That is why the creation of a duplicative, elastic and scalable monitoring system for monitoring the operating parameters of heavy machines and processes significantly supports the work of the staff and their handling of tasks related to the planning repair activities, delivery of spare parts, avoidance of critical work modes leading to sudden catastrophic consequences and unexpected production shutdowns.